Analysis of The Effect on Economic Growth, Foreign Investment, Population and Energy Consumption on Co2 in Asean Economies - Al-Azizi, Zuraida Hafsa; Rahmawati, Farida; Rokhmani , Lisa (PT. EQUATOR SINAR AKADEMIA, 2025)
ASEAN member states have proactively taken steps to address climate change issues at the national, regional and global levels. However, the rapid growth of the global economy and human activities on climate is increasing and has become a cause of environmental damage. This study aims to examine the effect of economic growth (GDP), foreign investment (FDI), population and energy consumption on CO2 emissions and examine the determinants of dynamic interaction of long- and short-term relationships using fixed effects panel data models and vector error correction models (VECM) for five ASEAN countries namely Indonesia, Malaysia, Philippines, Thailand and Vietnam using panel data with a time span of 1997 to 2020. The results of the fixed effects panel model test confirmed that economic growth, foreign investment and energy consumption affect CO2 emissions while population has no effect on CO2 emissions. In simultaneous testing, economic growth, foreign investment, population and energy consumption variables jointly affect CO2 in ASEAN countries. In addition, the VECM test results confirm that economic growth, foreign investment and energy consumption affect the CO2 of ASEAN countries in the long run, while population has no effect on CO2 of ASEAN countries in the long run. Other findings confirmed the existence of homogeneous causality relationship of GDP and FDI to CO2 and vice versa CO2 has homogeneous causality relationship to GDP and FDI. Population and Consumption have heterogeneous causality relationship to CO2. These variables are different in different situations and in different countries. The above results are expected that stakeholders can formulate appropriate policies.